2019
DOI: 10.1002/er.4550
|View full text |Cite
|
Sign up to set email alerts
|

The micro‐/nano‐PCMs for thermal energy storage systems: A state of art review

Abstract: Summary With advancement in technology—nanotechnology, various thermal energy storage (TES) materials have been invented and modified with promising thermal transport properties. Solid‐liquid phase change materials (PCMs) have been extensively used as TES materials for various energy applications due to their highly favourable thermal properties. The class of PCMs, organic phase change materials (OPCMs), has more potential and advantages over inorganic phase change materials (IPCMs), having high phase change e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 337 publications
0
63
0
Order By: Relevance
“…Typically, the microcapsules prepared using complex coacervation have better morphology, more uniform size, and better stability. e main steps in complex coacervation processes are as follows [114]: (1) PCMs are dispersed in an aqueous polymer solution to form the emulsion; (2) a second aqueous polymer solution with opposite charges is added, leading the shell material to deposit on the surface of the droplet by electrostatic attraction; and (3) cross-linking, desolation, or thermal treatment is employed to obtain stable microcapsules.…”
Section: Chemical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, the microcapsules prepared using complex coacervation have better morphology, more uniform size, and better stability. e main steps in complex coacervation processes are as follows [114]: (1) PCMs are dispersed in an aqueous polymer solution to form the emulsion; (2) a second aqueous polymer solution with opposite charges is added, leading the shell material to deposit on the surface of the droplet by electrostatic attraction; and (3) cross-linking, desolation, or thermal treatment is employed to obtain stable microcapsules.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…e sol-gel method is an economical and mild process to synthesize PCM microcapsules. e general steps in microcapsule preparation are as follows: (1) the reactive materials involving PCMs, precursor, solvent, and emulsifier, are uniformly dispersed in a continuous phase to form a colloidal solution by hydrolysis reaction; (2) through condensation polymerization of monomers, a gel system with a three-dimensional network structure is formed; and (3) the microcapsules are formed after drying, sintering, and curing processes [114]. Sol-gel methods are usually used to synthesize inorganic shells, such as SiO 2 and TiO 2 shells.…”
Section: Physical-chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Many solid-liquid PCMs (S-LPCMs) include organic and inorganic or their binary/ternary which have been used in various TES purposes such as thermal regulation of buildings, thermal management of foods, storing of waste heat, and cooling of electronic systems and photovoltaic panels. [10][11][12][13] However, the usage of S-LPCMs involves some difficulties such as requirement of storage container to elude liquid leakage, phase separation in blend cases, and low thermal conductivity. Especially, storage containers used for holding S-LPCMs lead to considerable increment in thermal resistance between PCM and heat transfer fluid.…”
Section: Introductionmentioning
confidence: 99%
“…And the stable silica shell can withstand the solid-liquid phase change and volume change. 18,19 Lin et al 20 proposed a sol-gel method for preparing microcapsule with SiO 2 shell and octadecane core. It was found that the melting temperature was 28.32 C and the melting enthalpy of the microcapsule PCMs was 227.66 kJ kg −1 while the composites possessed good thermal stability due to the stable silica shell.…”
Section: Introductionmentioning
confidence: 99%